Analysis of Customer Satisfaction from Service Quality Dimensions Using Fuzzy-Carter Method (A Case Study at Bprs Khasanah Ummat Purwokerto) - Selitri Melina; Shafrani, Yoiz Shofwa (Wealth: Journal of Islamic Banking and Finance, 2022)
The primary goal of a business is to satisfy customers, so the caliber of this service has a significant impact on the success of a service company, specifically the creation of a sense of satisfaction with the services provided, where this will foster a loyal attitude of its customers and encourage positive and encouraging word of mouth as an assumption of customer satisfaction. By assessing the value gap between the services obtained and the standard of service expectations by clients, this researcher investigates the quality of services offered by BPRS Khasanah Ummat. This kind of research comprises quantitative associative research using the Fuzzy-CARTER approach to examine the connection between the caliber of services rendered and client satisfaction. The sample of this research is 286 active customers. The study's findings indicate that: 1) the level of customer satisfaction is measured across six CARTER dimensions, five of which customers are satisfied, namely compliance, assurance, reliability, tangibles, and responsiveness, but customers are not satisfied with the service on the dimension of empathy, indicating that improvements must be made by paying more attention to and understanding customer needs. 2) The overall level of customer satisfaction with service quality is good, and there is no gap between perceived perceptions and customer expectations.